If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + 2x)(3.25 + 2x) = 15 Multiply (3 + 2x) * (3.25 + 2x) (3(3.25 + 2x) + 2x * (3.25 + 2x)) = 15 ((3.25 * 3 + 2x * 3) + 2x * (3.25 + 2x)) = 15 ((9.75 + 6x) + 2x * (3.25 + 2x)) = 15 (9.75 + 6x + (3.25 * 2x + 2x * 2x)) = 15 (9.75 + 6x + (6.5x + 4x2)) = 15 Combine like terms: 6x + 6.5x = 12.5x (9.75 + 12.5x + 4x2) = 15 Solving 9.75 + 12.5x + 4x2 = 15 Solving for variable 'x'. Reorder the terms: 9.75 + -15 + 12.5x + 4x2 = 15 + -15 Combine like terms: 9.75 + -15 = -5.25 -5.25 + 12.5x + 4x2 = 15 + -15 Combine like terms: 15 + -15 = 0 -5.25 + 12.5x + 4x2 = 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. -1.3125 + 3.125x + x2 = 0 Move the constant term to the right: Add '1.3125' to each side of the equation. -1.3125 + 3.125x + 1.3125 + x2 = 0 + 1.3125 Reorder the terms: -1.3125 + 1.3125 + 3.125x + x2 = 0 + 1.3125 Combine like terms: -1.3125 + 1.3125 = 0.0000 0.0000 + 3.125x + x2 = 0 + 1.3125 3.125x + x2 = 0 + 1.3125 Combine like terms: 0 + 1.3125 = 1.3125 3.125x + x2 = 1.3125 The x term is 3.125x. Take half its coefficient (1.5625). Square it (2.44140625) and add it to both sides. Add '2.44140625' to each side of the equation. 3.125x + 2.44140625 + x2 = 1.3125 + 2.44140625 Reorder the terms: 2.44140625 + 3.125x + x2 = 1.3125 + 2.44140625 Combine like terms: 1.3125 + 2.44140625 = 3.75390625 2.44140625 + 3.125x + x2 = 3.75390625 Factor a perfect square on the left side: (x + 1.5625)(x + 1.5625) = 3.75390625 Calculate the square root of the right side: 1.9375 Break this problem into two subproblems by setting (x + 1.5625) equal to 1.9375 and -1.9375.Subproblem 1
x + 1.5625 = 1.9375 Simplifying x + 1.5625 = 1.9375 Reorder the terms: 1.5625 + x = 1.9375 Solving 1.5625 + x = 1.9375 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5625' to each side of the equation. 1.5625 + -1.5625 + x = 1.9375 + -1.5625 Combine like terms: 1.5625 + -1.5625 = 0.0000 0.0000 + x = 1.9375 + -1.5625 x = 1.9375 + -1.5625 Combine like terms: 1.9375 + -1.5625 = 0.375 x = 0.375 Simplifying x = 0.375Subproblem 2
x + 1.5625 = -1.9375 Simplifying x + 1.5625 = -1.9375 Reorder the terms: 1.5625 + x = -1.9375 Solving 1.5625 + x = -1.9375 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5625' to each side of the equation. 1.5625 + -1.5625 + x = -1.9375 + -1.5625 Combine like terms: 1.5625 + -1.5625 = 0.0000 0.0000 + x = -1.9375 + -1.5625 x = -1.9375 + -1.5625 Combine like terms: -1.9375 + -1.5625 = -3.5 x = -3.5 Simplifying x = -3.5Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.375, -3.5}
| 3x-12=-12+3x | | c-d=f | | 10x/x-6-60/x-6 | | 27x^2/3 | | =7x+5(1-x) | | 6(q-3)=-4(q+2) | | 5=10z+2(-7/2z-1) | | 2x-2=6x+1 | | 2p=km-t | | 3(x-4)=-1/2(24-6x) | | x-(5-3x)=7x*4 | | -5p=100 | | (19x-5)+(x+7)= | | 72*3/2 | | 1.5+2.5x+x=25 | | 3x^3-6x^2-75x+150=0 | | 5/2x=35-x | | 4r-8=24 | | -2=4y+x | | 5=13z-(z-1) | | 7x+2(7x+16)=179 | | 16/4=2u | | (x^(7/2))^(3/7)=8 | | 9x+4-3x=36 | | 3x+5+4x-12=15x-27 | | -2x+10=12-3x | | 1-4(u-1)=0 | | 4y-4/8+26/2=1/4 | | 2x^3+4x^2-3x=0 | | 2+9p-3p=14 | | 8+((12+5)*4)/2 | | 4/3+y/2=5/2 |